Non-tariff barriers, enforcement, and revenues: The use of anti-dumping as a revenue generating trade policy - Igor Bagayev; Ronald B. Davies; Panos Hatzipanayotou; Panos Konstantinou; Marie Rau (University College Dublin, UCD School of Economics, 2017)
In contrast to developed countries, developing nations are especially reliant on trade taxes, particularly tariffs, as a source of government revenue. As such, tariff liberalization provides them with an incentive to switch towards other revenue generating trade barriers such as anti-dumping duties. The effectiveness of this is potentially limited due to the greater enforcement challenges with the exporter specific anti-dumping relative to broad-based tariffs. We examine this by estimating the impact of anti-dumping measures for 82 importing countries from 2008-2014. We find that anti-dumping's trade effects are larger for countries with greater policy enforcement, especially in low income countries. Although the results are somewhat sensitive to the measure of enforcement, our overall findings indicate that for countries with weak enforcement, tariff liberalization combined with a shift towards non-tariff barriers like anti-dumping is likely to lower government revenues and hamper their ability to provide the infrastructure and education needed for development.
Keywords: F13; F15; H27; 330; Non-tariff Barriers; Anti-dumping; Enforcement; Tax Revenues; Shadow Economy